The Relationship Between Leadership Style and Managers' Communication Patterns on Employee Performance, Job Satisfaction, and Organizational Commitment - Marhouni, Elahe; Pali, Samira (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The present study aimed to examine the relationship between leadership style and managers' communication patterns on employee performance, job satisfaction, and organizational commitment.Methodology: The study is descriptive-survey in nature. The research population included all managers and employees of Pardis Petrochemical Company in the year 2023, from which 280 individuals were purposefully selected as the sample. The research instruments included the Multifactor Leadership Questionnaire (MLQ) by Bass and Avolio (1985), the Communication Skills Questionnaire (CKIJ) by Jerabek (2004), the Organizational Performance Questionnaire (ACHIEVE) by Hersey and Goldsmith (2003), the Job Satisfaction Questionnaire (JSQ) by Weiss, Dawis, England, and Lofquist (1967), and the Organizational Commitment Questionnaire (OCQ) by Allen and Meyer (1990). The method of analysis used in this study was structural equations.Findings:  The findings indicated that there is a relationship between managers' leadership styles and employee performance, job satisfaction, and organizational commitment (p < .05). Additionally, a relationship was found between managers' communication patterns and employee performance, job satisfaction, and organizational commitment (p < .05).Conclusion: It can be concluded that leadership style and managers' communication patterns have a significant impact on important aspects of organizational behavior, including employee performance, job satisfaction, and organizational commitment.